Handbook of organizational justice - Greenberg, Jerald; Colquitt, Jason (Lawrence Erlbaum Associates, 2005)
Matters of perceived fairness and justice run deep in the workplace. Workers are concerned about being treated fairly by their supervisors; managers generally are interested in treating their direct reports fairly; and everyone is concerned about what happens when these expectations are violated. This exciting new handbook covers the topic of organizational justice, defined as people's perceptions of fairness in organizations. The Handbook of Organizational Justice is designed to be a complete, current, and comprehensive reference chronicling the current state of the organization.